Maxillary Sinus Floor Augmentation with Autogenous Bone Graft Alone Compared with Alternate Grafting Materials: a Systematic Review and Meta-Analysis Focusing on Histomorphometric Outcome - Thomas Starch-Jensen; Daniel Deluiz; Niels Henrik Bruun; Eduardo Muniz Barretto Tinoco (eJournal of Oral Maxillofacial Research, 2020)
Objectives: The objective of present systematic review was to test the hypothesis of no difference in histomorphometric outcome after maxillary sinus floor augmentation with autogenous bone graft alone compared with alternate grafting materials applying the lateral window technique.